2008
DOI: 10.1007/s10979-007-9094-8
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of static and dynamic risk factors in the prediction of inpatient violence: Variable- and person-focused analyses.

Abstract: Although the construct of psychopathy is related to community violence and recidivism in various populations, empirical evidence suggests that its association with institutional aggression is weak at best. The current study examined, via both variable-level and group-level analyses, the relationship between standard violence risk instruments, which included a measure of psychopathy, and institutional violence. Additionally, the incremental validity of dynamic risk factors also was examined. The results suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
71
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 63 publications
10
71
2
1
Order By: Relevance
“…This is comparable to previous findings (Doyle, Dolan, & McGovern, 2002;Gray et al, 2003;McDermott, Edens, Quanbeck, Busse, & Scott, 2008). The predictive ability was in the poor towards moderate range only, which also may reflect good management of high-risk individuals based on in situ assessments.…”
Section: Discussionsupporting
confidence: 89%
“…This is comparable to previous findings (Doyle, Dolan, & McGovern, 2002;Gray et al, 2003;McDermott, Edens, Quanbeck, Busse, & Scott, 2008). The predictive ability was in the poor towards moderate range only, which also may reflect good management of high-risk individuals based on in situ assessments.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings, along with other recent studies (e.g. McDermott, Edens, Quanbeck, Busse, & Scott, 2008), contradict claims that remorselessness, callousness, and egocentricity are valid indicators of the likelihood of subsequent violence in institutional settings. In fact, to the extent that the negative associations between PPI Coldheartedness and institutional misconduct (see Footnote 4) prove to be replicable in future investigations, our results raise the possibility that emotional detachment (at least as assessed by the PPI) may even be a protective factor against certain forms of institutional misconduct (cf.…”
Section: Discussioncontrasting
confidence: 79%
“…The addition of an extreme affective state is also critical. Previous research has indicated as such: cluster analyses revealed that patients scoring high on the PCL-R and the NAS-PI were responsible for much of the aggression exhibited in a forensic facility (McDermott et al, 2008).…”
Section: Discussionmentioning
confidence: 97%